Negative Electrode Active Material and the Fabrication Method Thereof
Patent Information
- Application Number
- KR1020240097318
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-07-23
- Publication Date
- 2026-09-02
- Estimated Expiration
- 2044-07-23
Smart Images

Figure 112024080159621-PAT00004_ABST
Abstract
Description
Technology Field
[0001] The present disclosure relates to a negative electrode material for a lithium secondary battery and a method for manufacturing the same, and more specifically, to a natural graphite-based negative electrode material for a lithium secondary battery and a method for manufacturing the same. Background Technology
[0002] As the market for electronic devices such as mobile phones, laptops, and PCs grows, the market for lithium-ion batteries, their power source, is also expanding rapidly. Furthermore, as interest in environmental issues grows and the demand for eco-friendly vehicles like electric cars increases, there is a growing trend of research into lithium-ion batteries capable of meeting various applications.
[0003] Among the components of a lithium-ion battery, the negative electrode active material stores lithium ions during charging and plays a crucial role in determining charging speed and battery capacity. Carbon-based active materials are representative commercially used negative electrode active materials. Carbon-based active materials can be classified into graphitic carbon, such as natural graphite or synthetic graphite, and low-crystallinity carbon, such as non-graphitizable carbon or digraphitizable carbon.
[0004] Among these, natural graphite has high price competitiveness and a higher capacity than synthetic graphite, but it has the problem of low electrode density because the irreversible reaction caused by the exposed edge surface is large, the lithium ion diffusion path is limited due to the uniaxial orientation of the graphene layer, and it is easy to orient it in a planar shape on the current collector.
[0005] To address these issues, technologies are being developed to improve initial charge / discharge efficiency, electrode density, and high-rate characteristics by processing natural graphite into a spherical shape and forming a carbon coating layer on the surface of the spherical natural graphite; however, there is a need for the development of technologies for natural graphite-based anode materials with even better high-rate output characteristics. Prior art literature
[0006] Republic of Korea Published Patent No. 10-2023-0049285 The problem to be solved
[0007] One aspect of the present invention is to provide a natural graphite-based cathode material having improved high-rate output characteristics and a method for manufacturing the same.
[0008] Another aspect of the present invention is to provide a natural graphite-based cathode material having improved immersion properties and a method for manufacturing the same.
[0009] The problems of the present invention are not limited to those described above. A person skilled in the art to which the present invention pertains will have no difficulty understanding additional problems of the present invention from the overall contents of this specification. means of solving the problem
[0010] A method for manufacturing a negative electrode material for a lithium secondary battery according to one embodiment of the present invention comprises: a step of producing pressurized natural graphite by isotropically pressing primary spherical natural graphite; a step of producing crushed natural graphite by crushing the pressurized natural graphite; and a step of producing spherical natural graphite by re-sphericalizing the crushed natural graphite through mechanical processing.
[0011] A manufacturing method according to one embodiment may further include the step of spheroidizing natural graphite having an anisotropic shape before isotropic pressing to produce the primary spheroidized natural graphite.
[0012] A manufacturing method according to one embodiment may further include the step of forming a carbon-containing surface layer on the spherical natural graphite after the resphericalization.
[0013] In one embodiment, the spheroidization, the re-spheroidization, or each of the spheroidization and re-spheroidization can be performed by rotary processing using airflow.
[0014] In one embodiment, rotary processing using the above airflow can be performed by removing fine particles from inside to outside the processing space where the processing is performed.
[0015] In one embodiment, the isostatic pressing may include cold isostatic pressing (CIP) or hot isostatic pressing (HIP).
[0016] In one embodiment, the pressure during isotropic pressurization may be 100 to 500 MPa.
[0017] A negative electrode material for a lithium secondary battery according to one embodiment of the present invention comprises a core of spherical natural graphite and a surface layer containing carbon, has an activity defined by Formula 1 below of 1.3 to 2.5, and an orientation index defined by Formula 2 below of 65 or higher.
[0018] (Equation 1)
[0019] Activity = [S BET / D 50 ] × P
[0020] S in Equation 1 BET ε is the BET specific surface area (m²) of the cathode material 2 / g) and, D 50 is the cumulative volume-based median diameter (μm) of the cathode material, and P is the porosity (%) of the cathode material measured by the mercury intrusion method.
[0021] (Equation 2)
[0022] Orientation index = I 110 / I 004 × 100
[0023] In Equation 2, I 110 I is the maximum intensity of the (110) peak in the X-ray diffraction pattern of the cathode material, and I 004 is the maximum intensity of the (004) peak in the same X-ray diffraction pattern.
[0024] The cathode material according to one embodiment may have a surface curvature rate defined by Formula 3 below of 10.0% to 13.0%.
[0025] (Equation 3)
[0026] Curvature Ratio = [1 - 1 / R] × 100
[0027] In Equation 3, R is roughness, which is the ratio (P / CP) of the particle perimeter (P) to the convex perimeter (CP), 0.8D 50 to 1.2D 50 It is a roughness for a cathode material having the size of
[0028] In one embodiment, the above S BET / D 50 It can be 0.13 to 0.16.
[0029] In one embodiment, the above D 50 It can be 10 to 25 μm.
[0030] In one embodiment, the tap density of the cathode material is 1.00 to 1.30 g / cm³ 3 It could be.
[0031] In one embodiment, the surface layer may be a carbon layer.
[0032] One embodiment of the present invention includes a negative electrode for a lithium secondary battery comprising the negative electrode material described above. Effects of the invention
[0033] The cathode material according to one embodiment can have improved high-rate output characteristics.
[0034] The cathode material according to one embodiment may have improved electrolyte immersion characteristics.
[0035] The various and beneficial advantages and effects of the present invention are not limited to those described above and will be more easily understood in the process of explaining specific embodiments of the present invention. Brief explanation of the drawing
[0036] Figure 1 is a scanning electron microscope image showing the shape of the cathode material prepared in Comparative Example 1. Figure 2 is a scanning electron microscope image showing the shape of the cathode material prepared in Example 1. Specific details for implementing the invention
[0037] Preferred embodiments of the present invention will be described below with reference to the attached drawings. However, embodiments of the present invention may be modified in various other forms, and the scope of the present invention is not limited to the embodiments described below.
[0038] In addition, embodiments of the present invention are provided to more fully explain the present invention to those with average knowledge in the relevant technical field.
[0039] In drawings, the shapes and sizes of elements may be exaggerated for clearer explanation.
[0040] In describing the embodiments of the present invention, if it is determined that a detailed description of known technology related to the present invention may unnecessarily obscure the essence of the present invention, such detailed description will be omitted. Furthermore, the terms described below are defined considering their functions in the present invention, and these may vary depending on the intentions or conventions of the user or operator. Therefore, such definitions should be based on the content throughout this specification. The terms used in the detailed description are merely for describing the embodiments of the present invention and should not be limited in any way. Unless explicitly stated otherwise, expressions in the singular form include the meaning of the plural form.
[0041] In this description, expressions such as “include” or “equipped” are intended to refer to certain characteristics, numbers, steps, actions, elements, parts or combinations thereof, and should not be interpreted to exclude the existence or possibility of one or more other characteristics, numbers, steps, actions, elements, parts or combinations thereof other than those described.
[0042] Unless otherwise specifically defined in the specification of the present invention, % units mean weight %.
[0043] Additionally, throughout the specification, when it is said that one part is 'connected' to another part, this includes not only cases where they are 'directly connected,' but also cases where they are 'indirectly connected' with other elements in between.
[0044] The present invention will be described in detail below through each embodiment or example of the invention. It should be noted that each embodiment or example described in this specification is not limited to a single embodiment or example, but may also be combined with other embodiments or examples. Accordingly, the citation of claims in the patent claims is merely an example of an embodiment, and the technical concept of the present invention should not be interpreted as being limited only to a combination with the cited claims; rather, combinations with various claims are also included within the scope of the technical concept of the present invention.
[0045] The inventors conducted research on the crystallographic isotropy of natural graphite through mechanical spheroidization and the densification of the graphite structure by isotropic pressing. During this process, it was confirmed that there is a limit to the improvement in crystallographic isotropy when natural graphite itself, which has an anisotropic shape (e.g., flake-like) prior to mechanical spheroidization, is spheroidized by isotropic pressing. Furthermore, it was confirmed that while it is possible to manufacture natural graphite with improved crystallographic isotropy and a dense structure by densifying the spheroidized natural graphite by isotropic pressing after mechanical spheroidization, the specific surface area of the manufactured natural graphite becomes excessively low, resulting in a reduced active surface area in contact with the electrolyte and poor water penetration resistance when implemented as an active material layer.
[0046] Accordingly, through continuous research aimed at resolving the issues of low active area and low penetration resistance, it was discovered that the primary cause of low penetration resistance is the particle shape of isotropically pressurized natural graphite. Furthermore, it was found that even though the graphite structure exhibits enhanced crystallographic isotropy upon isotropic pressurization, flat planar regions are formed on the particle surface, consisting mainly of graphite basal planes. This inhibits the intrusion of lithium ions through the surface, acting as a cause that reduces high-rate power characteristics along with the low specific surface area.
[0047] Based on these findings, the inventors have established a technology for manufacturing spherical natural graphite having pliability and specific surface area comparable to mechanically spherical natural graphite, and having crystallographic isotropy and a curved surface comparable to isotropically pressurized natural graphite, thereby completing the present invention.
[0048] A method for manufacturing a negative electrode material for a lithium secondary battery according to the disclosure includes the step of producing pressurized natural graphite by isotropically pressing a primary spherical natural graphite; the step of producing crushed natural graphite by crushing the pressurized natural graphite; and the step of re-sphericalizing the crushed natural graphite through mechanical processing.
[0049] The manufacturing method according to the first disclosure can significantly improve the crystallographic isotropy of natural graphite by isotropically pressurizing the spheroidized natural graphite (primary spheroidized natural graphite). Furthermore, by crushing the isotropically pressurized natural graphite and then mechanically processing the crushed natural graphite to respheroidize it, the particle shape, which is macroscopically angular with a flat surface due to isotropic pressure, can be transformed into a curved particle shape, or substantially a curved spherical shape. Additionally, by inducing an artificial springback effect through the mechanical force applied to the natural graphite during the respheroidization process, a large number of channels through which the electrolyte can permeate can be created along with a change in the particle shape of the natural graphite. In terms of physical properties, the creation of channels through which the electrolyte can permeate can be represented by an increase in the specific surface area and an increase in open pores.
[0050] As described above, by isotropically pressurizing and crushing the primary spherical natural graphite and then re-sphericalizing the natural graphite through mechanical processing, the advantages obtained by isotropic pressurization and mechanical sphericalization of natural graphite are maintained, while the disadvantages caused by isotropic pressurization are resolved, that is, spherical natural graphite having excellent penetrating properties, a specific surface area favorable for lithium diffusion (movement), and significantly excellent crystallographic isotropy can be produced.
[0051] A manufacturing method according to one embodiment may further include the step of spheroidizing natural graphite having an anisotropic shape before isotropic pressing to produce primary spheroidized natural graphite.
[0052] A manufacturing method according to one embodiment may further include the step of forming a carbon-containing surface layer on the reshaped natural graphite after reshaping.
[0053] In describing each step of the manufacturing method below, for a clearer understanding and explanation, natural graphite having an anisotropic shape may be referred to as 'raw material,' the spheroidization process of the raw material as 'primary spheroidization' or 'primary spheroidization process,' the natural graphite obtained by spheroidization of the raw material (the aforementioned primary spheroidized natural graphite) as 'primary spheroidal graphite,' the pressurized natural graphite obtained by isotropic pressurization of the primary spheroidal graphite as 'dense graphite,' the natural graphite from which the dense graphite has been broken down as 'broken graphite,' the spheroidization process of the broken graphite as 're-spheroidization' or 're-spheroidization process,' the natural graphite obtained by re-spheroidization (re-spheroidized natural graphite) as 'core' or 'spherical natural graphite,' and the step of forming the surface layer may be collectively referred to as the 'coating step.'
[0054] 1st spheroidization stage
[0055] The raw material may be natural graphite particles having an anisotropic shape. The anisotropic shape is defined by the size (length) l in the three axial directions with respect to three mutually orthogonal axes (x, y, z) with the center of the particle as the origin. x , l y and l z The longest length among them (for example, l x ) the shortest length (for example, l z It can refer to a shape where the aspect ratio divided by ) is 2 or greater, specifically 3 or greater. In this case, experimentally l x , l y and l z It can be measured through image observation, including conventional scanning electron microscope observation. Representative examples of anisotropic shapes include plate shapes and / or flake shapes. As a practical example, the raw material may be flaky natural graphite that can be easily and densely bonded, folded, and / or assembled by mechanical processing, but is not limited thereto.
[0056] The first spheroidization process may be mechanical processing of the raw material, and mechanical processing may refer to a process of mechanically adjusting the shape of natural graphite (raw material) having an anisotropic shape into a spherical shape by applying mechanical force.
[0057] The first spheroidization can be performed by a spheroidization method by mechanical processing that is commonly known in the field of secondary batteries. Representative examples of mechanical processing include Air Classifying milling, Spheronizing milling, Grinding milling, Mechanofusion milling, Planetary milling, Hybridization milling, Shape milling, and High Speed milling. The mechanical processing can be performed under known conditions, for example, at a rotational speed of 500 to 4000 rpm, and can be performed for 5 to 60 minutes, but is not limited thereto.
[0058] In a favorable example, the mechanical processing during the first spheroidization may be rotary processing using an airflow. Rotary processing using an airflow may mean mechanical processing in which a raw material containing natural graphite is moved by a rotary airflow, and mechanical forces such as impact compression, friction, and / or shear force are applied to the natural graphite.
[0059] In a more advantageous example, rotary processing using airflow can be batch processing. That is, rotary processing using airflow can be performed in a batch manner. The statement that rotary processing is performed in a batch manner means that the input of raw materials, the mechanical processing of raw materials, and the production of spherical graphite are completed within the same processing space. In other words, 'batch processing' may mean that within a pre-defined same processing space, raw materials are input, the sphericalization of raw materials begins and is completed, and spherical natural graphite is produced.
[0060] In a more advantageous example, the first spheroidization may be a batch processing using a batch device (batch spheroidization device) described below. By performing the first spheroidization by batch processing using a batch device, the crystallographic isotropy of natural graphite can be significantly improved through first spheroidization and isotropic pressing, and dense graphite with a high degree of spheroidization can be produced. Specifically, if the degree of spheroidization of the natural graphite produced by the first spheroidization is low and the isotropy of the first-spheroidized natural graphite is low, there is a risk that the isotropy will be reduced by isotropic pressing into a shape with increased anisotropy, such as an elongated shape or a disk shape, compared to the first-spheroidized state, and the improvement in isotropy will be minimal. In addition, in the case of dense graphite having a highly anisotropic shape such as a rectangular or disc shape, very harsh mechanical processing may be required for respheroidization, and there is a risk that during such harsh mechanical processing, the effect of isotropic pressure applied after the first spheroidization will disappear and only the effect of respheroidization will remain.
[0061] However, when performing primary spheroidization through batch processing using the batch device described below, spheroidization can be achieved that is substantially similar to a perfect sphere with excellent isotropy. As a result, through subsequent isotropic pressing, the isotropy is significantly improved compared to the primary spheroidization, and dense graphite (disintegrated graphite) can be obtained as square, angular particles.
[0062] Square angular particles should not be interpreted as being limited to angular particles having flat surfaces in the shape of a square. Square angular particles can be interpreted as having a flat surface area, wherein the minimum square size in which the particle is in contact with and within which the particle can be located is a square or a quasi-square, based on the two-dimensional image of the particle. In this case, a quasi-square may mean that the ratio (L1 / L2) of the length of the relatively longer side (L1) to the length of the other relatively shorter side (L2) in the minimum square size in contact with and surrounding the particle described above is 1 to 1.6, specifically 1 to 1.4, and more specifically 1 to 1.2. Here, the L1 / L2 ratio may be the average value of values measured for each fragmented graphite particle for at least 100, substantially 500 to 20,000 fragmented graphites. The flat surface region, which takes on a flat shape by applying pressure, may be located in different directions from the center of the sphere, specifically in 2 to 10 different directions, specifically in 2 to 8 different directions, and the flat surface region may be indented relative to the surrounding surface region, protrude, and / or be connected to the surrounding surface region. In this case, the region connecting the flat surface regions (edge region) may be a sharp edge formed by the flat surface regions meeting directly, or it may be a curved surface (curved edge).
[0063] In a batch-type device, the processing space may be defined by a spherical gun case that partitions the internal and external spaces, and the internal space of the spherical gun case may correspond to the processing space. In the processing space where rotary processing using airflow is performed, a processing unit may be located that includes a rotation axis and a rotating member that generates a rotational airflow when coupled with the rotation axis. The rotating member may include a ring-shaped plate (a hollow circular plate). A rotation axis may be located at the center of the ring-shaped plate, and the plate and the rotation axis may be coupled to each other by a plurality of bar-shaped connecting members. Specifically, the rotating member may include a plurality of ring-shaped plates located spaced apart from each other in the axial direction of the rotation axis, more specifically, two to three ring-shaped plates. The ring-shaped plates may include a hammer capable of applying physical impact to natural graphite. In detail, each ring-shaped plate may be equipped with a plurality of hammers at regular intervals along the circumferential direction centered on the rotation axis. The shape of the hammer may be an angular shape or a curved shape based on its cross-section. Representative examples of angular shapes include, based on cross-section, triangles, squares, or pentagons, and representative examples of curved shapes include, based on cross-section, circles, truncated circles, ellipses, and truncated ellipses, but are not limited thereto. Additionally, a circular plate located below the rotating member may be further provided on the rotation axis. Natural graphite can be easily introduced into the space between the rotating member (or hammer) and the inner surface (or liner) of the spherical gun case through this circular plate. Furthermore, a plurality of liners spaced apart from each other may be provided on the inner surface of the spherical gun case located at least outside the processed part.
[0064] When rotary processing is performed in a batch manner, fine particles can be removed during rotary processing using airflow. To this end, the processing space may be connected to a dust collection unit for removing fine particles within the processing space. The dust collection unit may have fluid suction capabilities through a conventional fluid flow generating device, such as a blower, to suction and remove fine particles within the processing space. As a practical example, the dust collection unit may include a classifier connected to the processing space, and fine particles passing through the classifier may be sucked out of the processing space and removed. The classifier may be an airflow classifier, and the airflow classifier may be a swirling airflow (centrifugal) classifier. As a practical example, the swirling airflow classifier may include a forced vortex classifier. Examples of forced vortex classifiers include, but are not limited to, turboflex, super separators, and micro separators.
[0065] The first spheroidization, performed by a batch process using a batch device, can be carried out for 5 to 40 minutes at a rotational speed of 800 to 3000 rpm, specifically 1500 to 2500 rpm.
[0066] Primary spherical graphite produced by a batch process using the aforementioned batch apparatus may have a degree of sphericity of 0.85 or higher, specifically 0.87 or higher, and substantially the degree of sphericity of the primary spherical graphite may be 0.91 or lower, more substantially 0.90 or lower.
[0067] Advantageously, primary spherical graphite is 0.85 g / cm³ 3 From 1.00 g / cm³ 3 It can have the following tap density. Tap density is a physical property influenced by various factors such as the shape, surface characteristics, degree of aggregation (bonding), internal pore structure, and porosity of primary spherical graphite. 0.85 g / cm³ 3Primary spherical graphite that does not reach [a certain level] may be in a state where sphericity is not substantially complete; that is, it may contain a large number of internal pores and the assembly and bonding between natural graphite fragments are not firmly formed. Such primary spherical graphite exhibits low crystallographic isotropy and is at risk of deforming into rectangular particles under isotropic pressure due to the wedge-shaped internal pores between graphite fragments. On the other hand, the tap density is 1.00 g / cm³ 3 If it exceeds [value], there is a risk that the degree of isotropy improvement due to isotropic pressure will be minimal due to the excessively dense primary spherical graphite.
[0068] Accordingly, according to one favorable example, primary spherical graphite satisfying the aforementioned degree of sphericity and tap density is produced by using a batch process with a batch device, and then isotropically pressurized thereon, thereby producing square dense graphite (and fragmented graphite) having significantly improved isotropy.
[0069] The size of the raw material used for the first spheroidization may be any size that is typically used for the spheroidization of natural graphite.
[0070] However, in the case where spheroidization is performed through batch processing using a batch device according to the aforementioned advantageous example, the median diameter (D) based on the cumulative volume of the raw material 50 ) can be at the level of tens of micrometers. Specifically, the D of the raw material 50 The µm can be 15 to 40 μm, specifically 18 to 35 μm, more specifically 18 to 30 μm.
[0071] Isotropic pressurization stage
[0072] Isostatic pressing can be cold isostatic pressing (CIP) or hot isostatic pressing (HIP), and as a practical example, it can be cold isostatic pressing.
[0073] In order to produce dense graphite in the form of square, angular particles, which has significantly high crystallographic isotropy and is simultaneously densified by isotropic pressing, the pressure (P during isotropic pressing) t ) may be 100 to 500 MPa, specifically 150 to 400 MPa, more specifically 200 to 350 MPa.
[0074] When isotropically pressurized, the preset pressure (P t The time for which ) is applied is sufficient if it is the time required for the natural graphite fragments constituting the primary spherical graphite to deform, for the graphite structure to densify, and for crystallographic isotropy to improve. Specifically, since the deformation of the natural graphite fragments due to pressurization is immediate, the pressure (P during isotropic pressurization) t The time for which ) is applied is sufficient if it is approximately the time required for the pressure applied from the surface of the primary spherical graphite to be stably transmitted into the interior. As a practical example, pressure (P t The time for which ) is authorized may be 10 seconds to 20 minutes, specifically 30 seconds to 15 minutes, more specifically 1 minute to 10 minutes, but is not limited thereto.
[0075] When isotropically pressurized, the pressure increase up to the set pressure (P1) can be performed at a controlled pressure increase rate. Specifically, in order to stably secure the improvement of the orientation index by isotropically pressurized, the pressure increase can be performed at a pressure increase rate of 10 to 100 MPa / min when isotropically pressurized.
[0076] Disintegration stage
[0077] After isotropic pressurization is performed, a disintegration step can be performed to disintegrate the natural graphite particles aggregated by the pressurization.
[0078] The disintegration step can be performed by applying physical impact. As a specific example, the disintegration step can be performed using equipment that utilizes physical impact, such as a jet mill, an air classifier mill (or air current classification mill), or a roller mill. Specifically, a jet mill disintegrates particles by using a high-pressure airflow to collide with them, an air classifier disintegrates particles and classifies them according to specific gravity using an airflow, and a roller mill disintegrates particles by feeding them between two or more rollers rotating in opposite directions and compressing and crushing them.
[0079] For effective disintegration, the disintegration step may include a coarse grinding step and a fine grinding step. Specifically, the disintegration step may include a coarse grinding step for grinding a lump of natural graphite aggregated by isotropic pressure into a coarse powder, a fine grinding step for grinding the coarse powder into a fine powder, and a step of disintegrating by applying physical impact to the fine powder.
[0080] As a practical example, the coarse grinding step involves agglomerated natural graphite lumps by isotropic pressing to a cumulative volume-based median diameter (D) of 10 to 50 mm. 50 ), specifically, a cumulative volume-based median diameter (D) of 10 to 30 mm. 50 It may be a step of grinding into coarse powder. After coarse grinding is performed, in the fine grinding step, the coarse powder is based on a cumulative volume-based median diameter (D 50 The material may be ground into fine powder of less than 10 mm and broken down into individual graphite particles (broken particles) by applying physical impact to the fine powder. However, this is merely a specific grinding condition for faster and more effective breaking, and the present invention is not limited by the breaking method. Of course, if necessary, after breaking, further classification such as air stream classification and / or sieving classification may be performed to remove unbroken aggregated particles or fine particles that may be generated during breaking.
[0081] Reshaping stage
[0082] After the disintegration step is performed, a step of manufacturing spherical natural graphite by reshaping the disintegrated graphite through mechanical processing (mechanical force) can be performed.
[0083] Respherification can also be performed by a spherification method by mechanical processing that is commonly known in the field of secondary batteries. Respherification can be performed independently of primary spherification by one or more methods selected from the group of Air Classifying milling, Spheronizing milling, Grinding milling, mechanofusion milling, planetary milling, Hybridization milling, Shape milling, and high speed milling, but is not limited thereto. Respherification can be performed independently of primary spherification at a rotational speed of 500 to 4000 rpm and for 5 to 60 minutes, but is not limited thereto.
[0084] In one advantageous example, the reshaping may also be rotary machining using airflow. In a more advantageous example, rotary machining using airflow for reshaping may also be performed in a batch manner.
[0085] In a more advantageous example, reshaping can be performed as a batch process using a batch device (batch shaping device) that is substantially the same as the first shaping.
[0086] The batch process using the aforementioned batch device is advantageous because mechanical forces, including impact compression, friction, and / or shear force, can be applied to the particles in all directions, thereby allowing flat surface areas and edge areas to be easily processed into curved surfaces. In addition, the batch process using the aforementioned batch device is advantageous because reshaping can be achieved in a shorter time with weaker mechanical forces, thereby preventing the formation of an excessive number of open pores.
[0087] Respherification performed by a batch process using a batch device can be performed under conditions more relaxed than primary spherification, that is, at a lower rpm than primary spherification and for a shorter time than primary spherification. Specifically, respherification can be performed for 3 to 20 minutes at a rotational speed of 500 to 1800 rpm, specifically 800 to 1500 rpm.
[0088] The curvature of flat surface regions and the increase in open pores due to respheroidization reduce the fraction in which crystal planes of the basal plane overlap to form a macroscopic plane, thereby enabling omnidirectional diffusion of lithium ions and increasing the contact area with the electrolyte, which enables the smooth movement and diffusion of lithium ions into and / or from the particles.
[0089] Coating step
[0090] After manufacturing spherical natural graphite (core) by respherification, a coating step can be performed to form a carbon-containing surface layer on the spherical natural graphite. Through this, a surface layer containing carbon and surrounding the spherical natural graphite can be formed.
[0091] In detail, the coating step may include the step of mixing and heating spherical natural graphite with a carbon precursor. The carbon precursor may be one or more selected from the group consisting of isotropic pitch, anisotropic pitch, heavy oil, light oil, polyvinyl alcohol (PVA), polyvinyl chloride (PVC), sucrose, phenol resin, furan resin, furfuryl alcohol, polyacrylonitrile, cellulose, styrene, polyimide, epoxy resin, and glucose, but is not limited thereto.
[0092] The mixing of spherical natural graphite and a carbon precursor may be mechanical mixing. For example, mechanical mixing may be one or more selected from the group consisting of ball milling, mechanofusion milling, shaker milling, planetary milling, atritor milling, shape milling, nauta milling, nobilta milling, high speed mixing, paddle mixing, ribbon mixing, Henschel mixing, corn type mixing, homo mixing, and a stirrer, but is not limited thereto. If necessary, mechanical mixing may be performed with a solvent for dissolving the carbon precursor mixed together, and independently thereof, mechanical mixing may be performed with the carbon precursor in a state where it has been melted or softened by heating. At this time, heating may include frictional heat during mechanical mixing.
[0093] When mixing, the mixing ratio of the carbon precursor mixed with the spherical natural graphite may be any amount sufficient to form a surface layer that stably covers the surface of the spherical natural graphite. As a specific example, the weight ratio of spherical natural graphite to carbon precursor may be 100:0.1 to 20, specifically 100:1 to 15, but is not limited thereto.
[0094] After mixing of spherical natural graphite and a carbon precursor is performed, a heat treatment to carbonize the carbon precursor may be performed. The heat treatment for carbonization may be performed at 600 to 1500°C in a hydrogen, nitrogen, argon, or mixed gas atmosphere, but is not limited thereto.
[0095] The present invention includes a negative electrode material for a lithium secondary battery manufactured by the manufacturing method described above.
[0096] cathode material
[0097] The negative electrode material for a lithium secondary battery according to the disclosure comprises a core of spherical natural graphite and a surface layer containing carbon, has an activity defined by Formula 1 below of 1.3 to 2.5, and an orientation index defined by Formula 2 below of 65 or higher.
[0098] (Equation 1)
[0099] Activity = [S BET / D 50 ] × P
[0100] S in Equation 1 BET ε is the BET specific surface area (m²) of the cathode material 2 / g) and, D 50 is the cumulative volume-based median diameter (μm) of the cathode material, and P is the porosity (%) of the cathode material measured by the mercury intrusion method.
[0101] (Equation 2)
[0102] Orientation index = I 110 / I 004 × 100
[0103] In Equation 2, I110 I is the maximum intensity of the (110) peak in the X-ray diffraction pattern of the cathode material, and I 004 is the maximum intensity of the (004) peak in the same X-ray diffraction pattern.
[0104] The activity of Equation 1 is an indicator representing the active area of the anode material that can directly receive lithium ions in contact with the electrolyte. The orientation index of Equation 2 is an indicator representing the crystallographic isotropy of the anode material.
[0105] The cathode material has remarkably excellent crystallographic isotropy with an orientation index of 65 or higher. This high isotropy can be obtained by mechanical spheroidization of natural graphite, advantageously by mechanical spheroidization using the aforementioned batch-type spheroidization device and isotropic pressing of the spheroidized natural graphite. Specifically, the orientation index of the cathode material may be 65 to 90, more specifically 70 to 90, and more specifically 75 to 85.
[0106] The cathode material has the aforementioned high isotropy, and at the same time, [S BET / D 50 ] × The activity defined as P may be 1.3 to 2.5, specifically 1.6 to 2.5, more specifically 1.9 to 2.4, and even more specifically 2.0 to 2.3. This activity is a high activity that is not substantially realized in natural graphite under isotropic pressure.
[0107] As described above, the cathode material according to one embodiment has enhanced activity and high crystallographic isotropy. Such high activity and excellent isotropy are advantageous as they can improve the high-rate characteristics of the cathode material.
[0108] In one embodiment, the BET specific surface area S of the cathode material BET (m 2 / g) based on the cumulative volume of the cathode material median diameter D 50 Ratio S divided by (㎛) BET / D 50The amount can be 0.13 to 0.16, specifically 0.14 to 0.16. S of the cathode material under a dense structure BET / D 50 The value can be primarily determined by the surface roughness of the cathode active material. Curvature of the cathode material particles increases surface roughness, and high surface roughness of the cathode material is advantageous as it enables the penetration of lithium ions in all directions. However, excessively high S BET / D 50 The value can cause adverse reactions with the electrolyte, so S BET / D 50 It is advantageous for the value to be 0.16 or less.
[0109] The cathode material according to one embodiment may have a surface curvature rate defined by Formula 3 below of 10.0% to 13.0%.
[0110] (Equation 3)
[0111] Curvature ratio = [1 - 1 / R] × 100
[0112] In Equation 3, R is roughness, which is the ratio (P / CP) of the particle perimeter (P) to the convex perimeter (CP), 0.8D 50 to 1.2D 50 It is a roughness for a cathode material having the size of
[0113] The curvature rate defined by Equation 3 is related to the shape of the cathode material particles. Specifically, the curvature rate decreases when the flat surface area increases, and increases when the curved surface area increases. As described above in the manufacturing method, the cathode material can have an increased curvature rate as the flat surface areas formed during isotropic pressing are transformed into curved surfaces by respheroidization.
[0114] As described above, the curvature rate is an indicator indicating the degree to which a flat surface is removed from the cathode material, that is, the degree to which a curved surface is formed. The curvature rate of the cathode material may be 10.0% to 13.0%, specifically 10.5% to 13.0%, more specifically 11.0% to 13.0%, and even more specifically 11.5% to 12.5%.
[0115] The roughness adopted in Equation 3 is not the roughness of the entire cathode material, but D, which is the median diameter based on the cumulative volume of the cathode material. 50 Based on, 0.8D 50 to 1.2D 50 It may be the roughness of the cathode material falling within the size range of D. 50 Standard 0.8D 50 to 1.2D 50 The roughness of particles within the size range is advantageous because it can represent the electrolyte immersion characteristics of the cathode material.
[0116] In one embodiment, the degree of sphericity of the cathode material may be 0.90 or higher, specifically 0.91 or higher, substantially 0.95 or lower, more substantially 0.93 or lower. The degree of sphericity of the cathode material is based on a projected image (2D image) of the cathode material, which is a three-dimensional particle, and is the circumference (C) of a circle having the same area as the projected image. ir ) the perimeter length (P) of the projected image rj The ratio divided by ) (C ir / P rj It can be defined as ). A cathode material with a high degree of sphericity is advantageous for high-density formation. At this time, through prior experiments, it was confirmed that even if the square, angular particles mentioned above are re-spherical in the manufacturing method, there is no significant difference in the degree of sphericity between the square, angular particles and the re-spherical particles. This means that the degree of sphericity is a physical property that is insensitive to the spherical shape of the cathode material.
[0117] In one embodiment, the median diameter (D) based on the cumulative volume of the cathode material 50The size of the anode material may be 10 to 25 μm, specifically 10 to 20 μm, more specifically 12 to 18 μm. This size of the anode material is advantageous for high-density anodes, allows for the formation of a stable open pore structure within the active material layer when implemented as an anode active material layer, and prevents excessive increase in the viscosity of the slurry during the electrode manufacturing process. The span of the anode material may be 0.5 to 1.3, specifically 0.6 to 1.1, more specifically 0.7 to 1.0, but is not limited thereto.
[0118] In one embodiment, the cathode material is 1.00 to 1.30 g / cm³ 3 , specifically 1.05 to 1.25 g / cm³ 3 , more specifically 1.10 to 1.25 g / cm³ 3 , more specifically 0.15 to 1.25 g / cm³ 3 of It can have a tap density. By having the aforementioned tap density, the cathode material can have improved immersion properties and its long-term life characteristics can be improved.
[0119] In the cathode material, the core, which is spherical natural graphite, may be a secondary particle in which natural graphite fragments are packed, folded, and / or assembled into a spherical shape with a sphericity of 0.90 or higher. Specifically, the spherical natural graphite may be a natural graphite particle in which natural graphite fragments are packed and assembled in a cabbage shape, randomly packed, folded, and / or assembled, or packed and assembled in a composite form of cabbage shape and random shape. In this case, an example of a composite form may be a form in which the central region of the particle is randomly assembled and the surface region is packed in a cabbage shape.
[0120] In detail, spherical natural graphite may be particles in which natural graphite fragments are joined, folded, and / or assembled by mechanical processing. That is, spherical natural graphite may be natural graphite in which a mechanical force is applied (mechanically processed) to natural graphite having an anisotropic shape, such as flakes, so that natural graphite fragments derived from natural graphite having an anisotropic shape are folded, bent, joined, and / or assembled, and the shape is mechanically adjusted to be spherical. In this case, the spherical natural graphite may mean particles with a degree of sphericity of 0.90 or higher, specifically 0.91 or higher, substantially 0.95 or lower, and more substantially 0.93 or lower.
[0121] Median diameter based on cumulative volume of spherical natural graphite (D 50 ) may be 10 to 25 μm, specifically 10 to 20 μm, more specifically 12 to 18 μm, and the cumulative volume-based median diameter (D) of the cathode material 50 It can be substantially the same as ).
[0122] As described above, the cathode material may comprise a core of spherical natural graphite and a surface layer containing carbon. Structurally, the cathode material may have a core-shell structure, where the spherical natural graphite corresponds to the core and the carbon-containing surface layer corresponds to the shell. In terms of manufacturing method, the surface layer may correspond to a coating layer that contains carbon and coats the surface of the spherical natural graphite.
[0123] The surface layer can cover the edges of the natural graphite crystals exposed to the surface of at least the spherical natural graphite. As a practical example, the cathode material may include spherical natural graphite and a surface layer covering at least a portion of the spherical natural graphite. As the spherical natural graphite is covered by a carbon-containing surface layer, the edges of the natural graphite contained in the spherical natural graphite can be prevented from being directly exposed to the surface of the cathode material, side reactions caused by the electrolyte can be suppressed, and irreversible reactions can be reduced.
[0124] The surface layer may be a carbon layer, and the carbon layer may be a disordered carbon layer. The disordered carbon layer may include soft carbon, hard carbon, or a mixture thereof. The thickness of the surface layer may be 5 to 200 nm, specifically 10 to 150 nm, more specifically 10 to 50 nm, but is not limited thereto.
[0125] cathode
[0126] The present invention includes a negative electrode for a lithium secondary battery containing a negative electrode material (natural graphite-based negative electrode material) manufactured by the manufacturing method described above.
[0127] The present invention includes a negative electrode for a lithium secondary battery containing the aforementioned negative electrode material (natural graphite-based negative electrode material).
[0128] The negative electrode according to the first disclosure is a negative electrode for a lithium secondary battery and comprises a current collector and a negative active material layer located on at least one surface of the current collector and containing the negative electrode material (natural graphite-based negative electrode material) described above.
[0129] The negative electrode active material layer may contain 95 to 99 weight percent of a negative electrode active material based on the total weight of the negative electrode active material layer. At this time, the negative electrode active material may contain the aforementioned negative electrode material (natural graphite-based negative electrode material) alone or a heterogeneous negative electrode material together with the aforementioned negative electrode material (natural graphite-based negative electrode material). Examples of heterogeneous negative electrode materials include artificial graphite-based negative electrode materials and / or silicon-based negative electrode materials (silicon, silicon oxide, silicon-silicon oxide composite, silicon-carbon composite, silicon alloy, etc.). When the negative electrode active material contains both the aforementioned negative electrode material (natural graphite-based negative electrode material) and the heterogeneous negative electrode material, the weight ratio of the graphite-based negative electrode material to the heterogeneous negative electrode material may be 100:1 to 100, but is not necessarily limited thereto.
[0130] The negative electrode active material layer may further include an additive containing an organic binder together with the negative electrode active material, and if necessary, the additive may further include a conductive material. In terms of achieving stable fixation between negative electrode active materials and between the negative electrode active material and the current collector by the organic binder without damaging the conductivity and open pore structure within the negative electrode active material layer, the negative electrode active material layer may contain 1 to 5 weight% of an organic binder, substantially 1 to 3 weight% of an organic binder. Additionally, if the negative electrode active material layer further contains a conductive material, the negative electrode active material layer may contain 0.5 to 3 weight% of a conductive material, substantially 0.5 to 2 weight% of a conductive material, but is not limited thereto.
[0131] The organic binder is sufficient if it is a polymer binder commonly used in the field of lithium secondary batteries to bind particulate negative electrode active materials together and to bind the negative electrode active material to a current collector. Practical examples of organic binders include, but are not limited to, polyvinyl alcohol, carboxymethylcellulose, hydroxypropylcellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, or mixtures thereof.
[0132] The conductive material is sufficient if it is a conductive additive commonly used to improve the conductivity of the anode in the field of lithium secondary batteries. Specifically, the conductive material may include point conductive materials, linear conductive materials, planar conductive materials, or mixtures thereof. Examples of point conductive materials include conductive carbon materials such as carbon black, acetylene black, Ketjen black, channel black, Farness black, lamp black, thermal black, etc.; metal particles such as copper, nickel, aluminum, silver, etc.; conductive polymer particles; core-shell particles of a non-conductive core and a conductive shell; etc. Examples of linear conductive materials include carbon nanotubes, conductive carbon fibers, metal fibers, or conductive polymer fibers, etc. Examples of planar conductive materials include graphene or reduced graphene oxide, etc., but are not limited thereto. As a practical example, the conductive material may include carbon black, and as another practical example, the conductive material may include carbon black and carbon nanotubes.
[0133] The cathodic density (electrode density) of the cathode is 1.20 to 1.90 g / cm³. 3 Level, specifically 1.50 to 1.90 g / cm³ 3 It may be, but is not limited to this.
[0134] The current collector is sufficient to be a conventional conductive material used to ensure smooth current flow to the negative electrode active material layer in the field of lithium secondary batteries. The current collector may be in the form of a foil, porous foil, foam, mesh, nonwoven fabric, a non-conductive material with a conductive coating layer, or a combination thereof, but is not limited thereto. The material of the current collector is sufficient to have high conductivity without causing chemical changes within the battery. Practical examples of the current collector include copper, stainless steel, aluminum, nickel, titanium, or alloys thereof, but are not limited thereto. The current collector may have a conventional thickness, a practical example being 3 to 500 μm, but is not limited thereto.
[0135] The negative electrode may be manufactured using a method commonly used for manufacturing negative electrodes in the field of lithium secondary batteries. For example, the negative electrode may be manufactured by applying a slurry containing a negative electrode active material, a binder, a solvent, and, if necessary, a conductive material to at least one surface of a current collector, followed by drying and rolling, but is not limited thereto.
[0136] The solvent may be any solvent commonly used in the field of lithium secondary batteries for forming a slurry for manufacturing a negative electrode. For example, the solvent may be dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, dimethylformamide (DMF), water, or a mixture thereof, but is not limited thereto.
[0137] The application of the slurry may be any method commonly used in the field of lithium secondary batteries to form an active material layer using a slurry. As a practical example, the application of the slurry may be performed by slot die coating, Meyer bar coating, gravure coating, comma coating, roll coating, blade coating, bar coating, dipping coating, etc.
[0138] lithium secondary battery
[0139] The present invention includes a lithium secondary battery comprising the aforementioned negative electrode.
[0140] A lithium secondary battery according to the first disclosure may include the aforementioned negative electrode, positive electrode, a separator interposed between the negative electrode and the positive electrode, and an electrolyte. Specifically, the secondary battery may include a positive electrode comprising a positive current collector and a positive active material layer located on at least one surface of the positive current collector, the aforementioned negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte that conducts lithium ions. The positive active material or composition of the positive current collector and the positive active material layer, the solvent or electrolyte salt of the separator and the electrolyte, or the concentration of the electrolyte salt, etc., are sufficient if they are materials or compositions conventionally adopted in lithium secondary batteries. Furthermore, the secondary battery may further include an electrode assembly comprising a positive electrode, a negative electrode, and a separator, and a sealable battery container in which the electrolyte is housed.
[0141] Based on the type of separator and electrolyte, the lithium secondary battery may be a lithium-ion battery, a lithium-ion polymer battery, or a lithium-polymer battery, and based on the shape, it may be cylindrical, prismatic, coin-type, or pouch-type, but is not limited thereto.
[0142] The physical properties described in the detailed description and claims were measured according to the 'analysis and measurement methods' below.
[0143] Analysis and Measurement Methods
[0144] (D 50 )
[0145] 0.01 g of the analyte was suspended in ethanol, and the prepared suspension was sonicated for 1 minute. Subsequently, the cumulative volumetric diameter distribution was measured using a conventional laser diffraction particle size distribution analyzer (e.g., Microtrac S3500). The median diameter D of the analyte. 50 represents the diameter at the position where the cumulative volume is 50% in the cumulative volume diameter distribution. The span value is (D 90 -D 10 ) / D 50It is defined as, and D 10 represents the diameter at the position where the cumulative volume is 10% in the cumulative volume diameter distribution, and D 90 represents the diameter at the position where the cumulative volume is 90% in the cumulative volume diameter distribution.
[0146] (Sphericality)
[0147] Sphericity was measured by ultrasonically dispersing 0.01 g of the substance to be analyzed in 5 mL of ethanol and using a particle shape analyzer (e.g., Flowcam 8100, Fluid Imaging Technologies) commonly used for particle shape analysis. The sphericity of a substance refers to the average value of the sphericity, and the average value of the sphericity is a statistical average value obtained by obtaining the sphericity of at least 500 particles, generally at least 1,000 particles, and substantially 1,000 to 10,000 particles, and averaging the obtained sphericity values.
[0148] (asperity)
[0149] Roughness was measured by ultrasonically dispersing 0.01 g of the analyte in 5 mL of ethanol and using a particle shape analyzer commonly used for particle morphology analysis (e.g., Flowcam 8100, Fluid Imaging Technologies). Using a particle size scattergram generated by a standard program equipped with data processing and analysis software for the particle shape analyzer, such as a visual spreadsheet, the minimum size of the particle group (major particle group) used for roughness measurement was 0.8D 50 and the maximum size is 1.2D 50 A particle group is selected to calculate the roughness of the particles belonging to the main particle group. The roughness of a material is the average of the roughness values for each of the main particle groups of 10 randomly selected cathode material powder samples.
[0150] As is known, the convex hull is a surface defined by an elastic band that stretches around the contour of a 3D particle, assuming the particle to be measured is surrounded by a virtual elastic band in a 2D image. The convex perimeter is the length of the perimeter of this convex hull, and the particle perimeter is the length of the actual particle's perimeter. Roughness is defined as the ratio of the particle perimeter in the captured image to the convex perimeter.
[0151] (BET specific surface area)
[0152] After performing pretreatment by drying the analyte at a vacuum of 0.1 Torr or less and a temperature of 300°C for 1 hour, the BET specific surface area (m²) was calculated using the BET method from the nitrogen adsorption isotherm of the pretreated analyte. 2 / g) was calculated. The nitrogen adsorption-desorption isotherm was measured using a specific surface area measuring device (e.g., ASAP 2400, Micromeritics) with a temperature of 77K using liquid nitrogen as the adsorbed nitrogen gas and a relative pressure (P / P0) measurement precision of 0.05.
[0153] (Tap density)
[0154] The tap density is the average value of the tap density measured twice on randomly selected samples, using a standard tap density measuring device (e.g., Quantachrome’s Autotap) based on ASTM B527, by placing 15g of the substance to be measured into a 50mL container and tapping 3000 times with a stroke length of 1.2cm (tapping speed = 284 times / min).
[0155] (Orientation Index)
[0156] X-ray diffraction patterns of the material to be measured are obtained using the θ-2θ method. Specifically, the X-ray diffraction pattern may be obtained using a conventional X-ray diffraction measuring device (e.g., RIGAKU, SmartLab SE) under conditions of a Cu Kα line, a scan step size of 0.03°, a scan speed of 0.05° / min, and a scan range of at least 2θ 75° to 80° and 2θ 53° to 56°. The scan range 2θ 75° to 80° is a range for measuring diffraction peaks due to the (110) plane (hereinafter, (110) peaks), and the scan range 2θ 53° to 56° is a range for measuring diffraction peaks due to the (004) plane (hereinafter, (004) peaks). The XRD measurement (raw) data can be noise removed (baseline setting), etc., by using a standard program equipped as a data processing and analysis program for the XRD device, such as the Highscore program. In the orientation index of the material being measured, (110) the intensity of the peak (I 110 ) is the maximum intensity of the (110) peak (maximum value of the peak), and the intensity of the (004) peak (I 004 ) is the maximum intensity (maximum value of the peak) of the (004) peak. The orientation index of the measured substance is the maximum intensity value (I) of the (110) peak. 110 ) (004) Maximum intensity value of the peak (I 004 The ratio divided by ) (I 110 / I 004 It is defined as × 100, %).
[0157] (Porosity)
[0158] The porosity of the material under measurement is measured by mercury porosimetry (also commonly referred to as mercury intrusion). Powdered cathode active material is pretreated by drying it at a vacuum of 0.1 Torr or less and a temperature of 150°C for 12 hours, after which it is measured using a conventional mercury porosimetry instrument (e.g., Autopore V 9620, Micromeritics). Measurements may be performed based on ASTM D 4284-83. When pressure is increased to infiltrate mercury into the internal pores of the material under measurement, the increment in pore volume (dV) through which mercury infiltrates at each pressure stage may be recorded. As is known, the applied pressure [is related to] the pore diameter (D Hg It is converted to ), and the pore size distribution (dV / dlogD) is derived from the pore volume increment (dV). Hg ) can be obtained. cm 3 Porosity in units of / g (P o ) is D in the pore size distribution Hg It can be obtained by accumulating the volume of pores within the reference size range of 3 nm to 2000 nm (the volume of mercury intruded into pores within the 3 nm-2000 nm size range). The porosity (%) of the material being measured is calculated by using a mercury porosity measuring instrument (e.g., Autopore V 9620, Micromeritics) to determine the ratio of the density (D) to the apparent volume (volume of active material particles when mercury has not penetrated into the active material particles) of the cathode active material. a Calculate ) and porosity (%) = D a × P o × It is calculated using the formula for 100.
[0159] (Saliva-like)
[0160] A slurry was prepared by adding each material to deionized water and mixing for 10 minutes so that the weight ratio of the material to be measured (cathode material prepared in Examples to Comparative Examples) : conductive carbon black (super-P) : carboxymethylcellulose (CMC) : styrene butadiene rubber (SBR) was 95.6 : 1.0 : 1.1 : 2.3; then, the prepared slurry was applied to copper foil, dried, and rolled to obtain an electrode density of 1.55 g / cm³ 3 Manufacture a test electrode.
[0161] A solution in which LiPF6 is dissolved at a concentration of 1 M in a mixed solvent with a mixed volume ratio of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) of 3:7 is used as the test electrolyte.
[0162] After dropping 1 drop of test electrolyte with a volume of 1 µL at five locations along the centerline of the test electrode, the time taken for the test electrolyte to be completely absorbed into the test electrode at each location is measured, and the average is calculated to determine the immersion time.
[0163] (Half cell)
[0164] A half cell is manufactured using the cathode material prepared in the examples to comparative examples.
[0165] Specifically, a slurry was prepared by adding the cathode active material, styrene butadiene rubber, carboxymethylcellulose, and carbon black (super-P) to deionized water and mixing for 10 minutes so that the weight ratio of cathode material : conductive carbon black (super-P) : carboxymethylcellulose (CMC) : styrene butadiene rubber (SBR) is 95.6 : 1.0 : 1.1 : 2.3; then, the prepared slurry was coated onto a copper (Cu) foil, dried, and rolled to obtain an electrode density of 1.55 g / cm³. 3 Manufacture the cathode of.
[0166] A coin-type 2032 half cell is fabricated using lithium foil as the counter electrode of the negative electrode. A porous polypropylene film is used as the separator, and as the electrolyte, a solution is used in which vinylene carbonate (VC) is added to a mixed solvent with a volume ratio of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) of 3:7 to a concentration of 1.0 wt%, fluoro-ethylene carbonate (FEC) is added to a concentration of 10 wt%, and LiPF6 is dissolved at a concentration of 1 M.
[0167] Hereinafter, the manufactured half cell is collectively referred to as the half cell with the same number as the specific example number or comparative example number in which the cathode material was manufactured. For example, a half cell manufactured using the cathode material manufactured in Example 1 is collectively referred to as the half cell of Example 1.
[0168] (Electrochemical properties using a half-cell)
[0169] The manufactured half cell is measured for high-rate characteristics after the formation stage. In the formation charging stage, it is charged to 0.005 V with a constant current (CC) of 0.1 C and then charged from 0.005 V to 0.005 C with a constant voltage (CV). In the formation discharging stage, it is discharged to 1.5 V with a constant current (CC) of 0.1 C. The charging and discharging in the formation stage are repeated three times.
[0170] After the formation phase was performed, to test the high-rate characteristics, the device was charged at 0.5C, 1.0C, or 3.0C to 0.005V / 0.005C under constant current / constant voltage (CC / CV) conditions at 25℃, and then discharged at 0.5C to 1.2V under constant current (CC) conditions. The charge capacity retention rate is the ratio (%) obtained by dividing the charge capacity charged at each C-rate by the charge capacity at 0.5C.
[0171] The present invention will be described in detail below through examples. However, it should be noted that the examples described below are intended merely to illustrate and embody the present invention and are not intended to limit the scope of the present invention. This is because the scope of the present invention is determined by the matters described in the patent claims and matters reasonably inferred therefrom.
[0172] In the example, the mechanical processing of natural graphite was performed using a batch-type spheroidizing device in which three ring-shaped plates equipped with multiple rectangular hammers are spaced apart from each other and fixed to a rotation axis, a disc is fixed at the bottom of the rotation axis along with the ring-shaped plates in the direction of gravity, and an air-flow classifier (classification point 2 μm) connected to a blower is located at the top of the spheroidizing case for fine particle removal.
[0173] (Example)
[0174] Using a batch-type spheroidizing device, flaky natural graphite (D 50 The raw material (24.1 μm) was spheroidized at 1900 rpm for 14 minutes to obtain primary spheroidized natural graphite (D 50 17.2 μm, sphericity 0.89, span 1.30, tap density 0.90 g / cm³ 3 Manufactured ).
[0175] Dense graphite was prepared by filling a molding mold with primary spheroidized natural graphite and then performing cold isostatic pressing. The cold isostatic pressing conditions were a pressurization rate of 50 MPa / min and a pressure of 300 MPa (P t ) and isotropic pressurization time of 5 minutes (P t It was the authorization time.
[0176] After cold isostatic pressing, in order to break up the particles that were clumped together, the particles were coarsely crushed to a size of 10-50 mm using a coarse grinder, finely crushed to a size of 10 mm or less using a pin mill, and then finally broken down the particles using an air stream classifier to obtain broken-down graphite broken down into individual particles.
[0177] Spherical natural graphite was produced by re-spherizing broken graphite at 1100 rpm for 15 minutes using the same batch spheroidizing device, and then removing fine and coarse particles through air stream classification and sieving.
[0178] 100 parts by weight of manufactured spherical natural graphite and 5 parts by weight of petroleum-based pitch with a softening point of 250°C were mixed using a stirrer for 10 minutes, and then the mixture was heat-treated at 1200°C for 5 hours to prepare a cathode material. D of the prepared cathode material 50 The value was 14.7 μm, the span value was 0.81, and the sphericity was 0.92.
[0179] (Comparative Example 1)
[0180] A cathode material was prepared in the same manner as in Example 1, except that respheroidization was not performed in Example 1, and the fragmented graphite fragmented after cold isostatic pressing was immediately mixed with petroleum-based pitch.
[0181] (Comparative Example 2)
[0182] A cathode material was prepared in the same manner as in Example 1, except that cold isostatic pressing was not performed in Example 1, the primary spheroidized natural graphite was immediately re-spheroidized, and the re-spheroidized natural graphite was mixed with petroleum-based pitch.
[0183] (Comparative Example 3)
[0184] In Example 1, a cathode material was prepared in the same manner as in Example 1, except that the primary spherical natural graphite was re-sphericalized under the conditions of Example 1, and then the re-spherical natural graphite was cold isostatically pressed under the conditions of Example 1, then crushed and mixed with petroleum-based pitch.
[0185] BET specific surface area (m²) of the cathode material prepared in the examples and comparative examples 2 / g) D 50 Ratio divided by (μm) (S in Table 1 BET / D 50 ), S BET / D 50Activity according to Equation 1, which is the value obtained by multiplying by the porosity (%), orientation index of the cathode powder according to Equation 2, curvature rate (%) according to Equation 3, and tap density (g / cm³) 3 The ), acupuncture time (sec) are summarized in Table 1.
[0186] (Table 1)
[0187]
[0188] As can be seen from the curvature rate in Table 1 and the scanning electron microscope image of the cathode material prepared in Comparative Example 1 in Figure 1, when the cathode material is prepared by the final process of cold isostatic pressing (and disintegration), macroscopically flat surface regions are formed on the natural graphite particles by cold isostatic pressing, and the curvature rate of the cathode material is significantly reduced.
[0189] However, according to one embodiment, when the primary spheroidized natural graphite is subjected to cooling and isotropic pressure and then re-spheroidized, as shown in Fig. 2, a scanning electron microscope image of the cathode material prepared in Example 1, it can be seen that the particle shape is adjusted to a curved surface, and a cathode material with significantly improved crystallographic isotropy and greatly increased activity is prepared as shown in Table 1.
[0190] In addition, when testing the penetration resistance to the electrolyte using a test electrode substantially equivalent to a negative electrode that can be adopted in a secondary battery, it was confirmed that the particle shape caused by isotropic pressure is the main factor hindering penetration resistance, as in Comparative Example 1 and Comparative Example 3, and it was found that the negative electrode material of the example with higher activity exhibits improved penetration resistance even though the curvature ratio is similar to that of Example 1 and Comparative Example 2.
[0191] Table 2 is a table summarizing the charge capacity retention rates of half cells manufactured using the cathode materials prepared in the examples and comparative examples. In Table 2, 1C is the ratio (%) of the charge capacity at 1C divided by the charge capacity at 0.5C, and 3C is the ratio of the charge capacity at 3C divided by the charge capacity at 0.5C.
[0192] (Table 2)
[0193]
[0194] Looking at Comparative Example 1 and Comparative Example 2 in Table 2, it can be seen that the cathode material of Comparative Example 1 has low crystallographic isotropy and flat surface regions, along with low activity, resulting in the worst high-rate output characteristics. It can be seen that the cathode material of Comparative Example 2 has improved crystallographic isotropy compared to Comparative Example 1, and its high-rate output characteristics are improved due to its curved surface and relatively high activity. Looking at Example 1 and Comparative Example 3, although both Example 1 and Comparative Example 3 have very high crystallographic isotropy (orientation index) of 78.9 and 75.1, respectively, it can be seen that the high-rate output characteristics of Comparative Example 3 are significantly worse than those of Example 1 due to the low activity and flat surfaces of the cathode material of Comparative Example 3.
Claims
Claim 1 A method for manufacturing a negative electrode material for a lithium secondary battery, comprising: a step of producing pressurized natural graphite by isotropically pressing a first spherical natural graphite; a step of producing crushed natural graphite by crushing the pressurized natural graphite; and a step of producing spherical natural graphite by re-sphericalizing the crushed natural graphite through mechanical processing. Claim 2 A method for manufacturing a negative electrode material for a lithium secondary battery according to claim 1, wherein the manufacturing method further comprises the step of spheroidizing natural graphite having an anisotropic shape before isotropic pressurization to produce the primary spheroidized natural graphite. Claim 3 A method for manufacturing a negative electrode material for a lithium secondary battery according to claim 1, wherein the manufacturing method further comprises the step of forming a surface layer containing carbon on the spherical natural graphite after the resphericalization. Claim 4 A method for manufacturing a negative electrode material for a lithium secondary battery, wherein, in claim 2, the spheroidization, the re-spheroidization, or each of the spheroidization and re-spheroidization is performed by rotary processing using an airflow. Claim 5 A method for manufacturing a negative electrode material for a lithium secondary battery according to claim 4, wherein fine particles are removed from inside to outside a processing space in which rotary processing using the above airflow is performed. Claim 6 A method for manufacturing a negative electrode material for a lithium secondary battery, wherein, in claim 1, the isostatic pressing comprises cold isostatic pressing (CIP) or hot isostatic pressing (HIP). Claim 7 A method for manufacturing a negative electrode material for a lithium secondary battery according to claim 6, wherein the pressure during isotropic pressing is 100 to 500 MPa. Claim 8 A negative electrode material for a lithium secondary battery comprising a core of spherical natural graphite and a carbon-containing surface layer, wherein the activity defined by Formula 1 below is 1.3 to 2.5 and the orientation index defined by Formula 2 below is 65 or higher. (Formula 1) Activity = [S BET / D 50 ] × P(S in Equation 1 BET is the BET specific surface area (m²) of the cathode material 2 / g) and, D 50 (where is the cumulative volume-based median diameter (μm) of the cathode material and P is the porosity (%) of the cathode material measured by the mercury indentation method)(Equation 2) Orientation index = I 110 / I 004 × 100(in Equation 2, I 110 I is the maximum intensity of the (110) peak in the X-ray diffraction pattern of the cathode material, and I 004 is the maximum intensity of the (004) peak in the same X-ray diffraction pattern) Claim 9 In claim 8, a negative electrode material for a lithium secondary battery having a surface curvature defined by the following Equation 3 of 10.0 to 13.0%. (Equation 3) Surface curvature = [1 - 1 / R] × 100 (In Equation 3, R is roughness, which is the ratio (P / CP) of the particle perimeter (P) to the convex perimeter (CP), 0.8D 50 to 1.2D 50 It is roughness applied to a cathode material having the size of Claim 10 In Clause 8, the above S BET / D 50 A negative electrode material for a lithium secondary battery, having a content of 0.13 to 0.
16. Claim 11 In Clause 8, the above D 50 A negative electrode material for a lithium secondary battery, having a thickness of 10 to 25 μm. Claim 12 In claim 8, the tap density of the cathode material is 1.00 to 1.30 g / cm³ 3 Phosphorus, anode material for lithium secondary batteries. Claim 13 A negative electrode material for a lithium secondary battery according to claim 8, wherein the surface layer is a carbon layer. Claim 14 A negative electrode for a lithium secondary battery comprising a negative electrode material according to any one of claims 8 to 13.
Citation Information
Patent Citations
Negative electrode active material for rechargeable lithium battery, method for preparing the same and rechargeable lithium battery including the same
KR1020140140323A
Material for negative electrode of lithium ionsecondary battery, process for manufacturing the same,and negative electrode using the same and lithium ionsecondary battery using the negative electrode
KR1020050009245A
Graphite particles for negative electrode active material, method for manufacturing the same, negative electrode active material including the same for rechargeable lithium battery, method for manufacturing the same, and rechargeable lithium battery
KR1020210115461A